[Memo from Peter Sparber to Samuel D Chilcote, Jr analyzing strategies related to "Operation Downunder" ] - Sparber, Peter G (Tufts Archival Research Center, 2007)
Memo from Peter Sparber to Samuel D Chilcote, Jr analyzing strategies related to the public smoking issue called "Operation Downunder" by Philip Morris staff. Deduces that "equal accomodation" legislation is too much of a comprimise. Discusses voluntary smoking restrictions. Includes quarterly reports of the corporate contact program and summaries of smoking restriction legislation and voluntary efforts.